Intraneural or extraneural ganglion cysts as a cause of cubital tunnel syndrome: A retrospective observational study - Yalikun, Ainizier; Yushan, Maimaiaili; Hamiti, Yimurang; Lu, Cheng; Yusufu, Aihemaitijiang (Frontiers in Neurology, 2022)
Purpose Cubital tunnel syndrome caused by ganglion cysts has rarely been reported. The purpose of this study was to evaluate the surgical treatment outcomes of a patient diagnosed with cubital tunnel syndrome caused by intraneural or extraneural cysts and to summarize our experience. Method In total, 34 patients were evaluated retrospectively from January 2011 to January 2020 with a follow-up of more than 24 months. Preoperative data, such as demographic data, clinical symptoms, physical examination findings, and laboratory tests, were all recorded and pre-operative and post-operative data were compared. The function was evaluated by the modified Bishop scoring system and the McGowan grade at the last follow-up. Results Improvement of interosseous muscle strength, the Visual Analog Scale (VAS), 2-point discrimination (2-PD), electromyogram (EMG) result, Wartenberg sign, claw hand, and weakness could be clearly observed in all patients. Extraneural cysts were completely removed and the pedicles of the cysts were ligated. Intraneural cysts were incised and drained, and part of their cyst walls were removed using a microsurgical technique. All patients underwent anterior subcutaneous transposition (AST). At the last follow-up, McGowan's (0-IIa) grade increased from seven patients (20.6%) preoperatively to 27 patients (79.4%); the excellent and good rate according to the modified Bishop scoring system was 82.4% (28 patients), and all patients had no symptoms of recurrence after surgery. Conclusion The treatment of cubital tunnel syndrome caused by intraneural or extraneural cysts achieved good long-term results through extraneural cyst resection or intraneural cyst incision and drainage combined with subcutaneous transposition. Early diagnosis and surgical treatment are essential for the patient's postoperative recovery.